MAKING AN APP - Higgins, Nadia (Mankato, Minnesota : Amicus and Amicus Ink, 2019)
"This book for elementary readers highlights the sequence of events from idea to a finished software application. Full-color photographs and a timeline support each step of the project's process, from the idea and coding a prototype to designing the app and uploading it to app stores like iTunes and Google Play. Includes glossary, index, and further resources"
Tap an App Plan It Out Designing the Look and Sound Put It All Together Get Ready to Launch Glossary Read More Websites Index
Includes bibliographical references (page 31) and index.
Keywords: Application software -- Juvenile literature; Computer programming -- Juvenile literature; Cell phones -- Juvenile literature. -- Programming